Spinel‐type Ni2GeO4 electrocatalyst for electrochemical ammonia synthesis via nitrogen reduction reaction under ambient conditions. (28th October 2021) - Kim, Dohun; Surendran, Subramani; Lim, Yoongu; Choi, Hyeonuk; Lim, Jaehyoung; Kim, Joon Young; Han, Mi‐Kyung; Sim, Uk
Summary: The electrochemical nitrogen reduction reaction (ENRR) is considered an environmentally‐friendly process for ammonia production under ambient conditions, compared to the conventional Haber‐Bosch method. However, the electrochemical synthesis of ammonia suffers from poor selectivity and low efficiency owing to constrained catalytic activity and the competitive hydrogen evolution reaction (HER). Spinel‐type solid materials have received considerable interest owing to their various applications in catalysis, energy storage, and optical devices. Particularly, mixed transition‐metal oxides with a formula of A2 BO4 exhibit improved catalytic activity owing to the presence of multiple balance sites for cations (A 2+/3+ and B 2+/3+/4+ ) in their structure. In this study, Ni2 GeO4 nanoparticles synthesized via a facile hydrothermal method were investigated as a novel electrocatalyst for the ENRR. X‐ray photoelectron spectroscopy confirmed the presence of octahedrally‐coordinated Ni 2+ and tetrahedrally‐coordinated Ge 4+ in the prepared spinel‐type Ni2 GeO4 material. Notably, the Ni2 GeO4 electrocatalyst achieved an excellent Faradaic efficiency of 3.57% and an ammonia yield rate of 3.06 μg h −1 cm −2 at −0.1 V vs RHE, owing to the enhanced charge transfer and chemical activity caused by charge polarization between the polyhedral units. The results of this primary investigation can inspire the development of Ni2 GeO4 ‐based electrocatalysts using innovative approaches to realize superior ENRR activity. Abstract : The electrochemical nitrogen reduction reaction for ammonia synthesis under ambient conditions is recognized as an environmental‐friendly strategy compared to the conventional Haber‐Bosh process. In this work, Ni2 GeO4 nanoparticles synthesized via a facile hydrothermal method were investigated as a novel electrocatalyst for nitrogen electroreduction. Notably, the Ni2 GeO4 electrocatalyst achieved an excellent Faradaic efficiency of 3.38% and an ammonia yield rate of 2.66 μg h −1 cm −2 at −0.1 V vs RHE, owing to the enhanced charge transfer and chemical activity caused by charge polarization between the polyhedral units.